Professional who attended childbirth and breastfeeding in the first hour of life - Laís Araújo Tavares Silva; Vânia Matos Fonseca; Maria Inês Couto de Oliveira; Kátia Silveira da Silva; Eloane Gonçalves Ramos; Silvana Granado Nogueira da Gama
ABSTRACT Objectives: To investigate the association between the professionals who attended vaginal delivery and breastfeeding in the first hour of life. Methods: This is a cross-sectional study with data from the Nascer no Brasil (Born in Brazil) survey, conducted in the 2011-2012 period. Data from 8,466 puerperae were analyzed using a logistic regression model with a hierarchical approach. Results: The proportion of mothers who breastfed at birth was higher in deliveries attended by nurses (70%). A nurse-assisted delivery was 64% more likely to breastfeed in the first hour of life. Other factors associated with the outcome: residing in the North; age less than 35 years; multiparity; prenatal guidance on breastfeeding in the first hour of life; birth at Baby-Friendly Hospital; companion at birth; and female newborn. Conclusions: Obstetrician nurse/nurse-assisted delivery was a significant independent factor associated with breastfeeding in the first hour of life, suggesting the importance of strengthening the role of the obstetrician nurse.